IMPROVING SEEDLING GROWTH AND TILLERING WITH OSMOTIC PRIMING TREATMENTS IN RICE CV. HAMZADERE AND OSMANCIK 97 - M. P. Kahriz; P. P. Kahriz (Journal of Animal and Plant Sciences, 2018)
Rice (Oryza sativa L.) is mainly cultivated in Thrace,  Black sea region and many land locked  small pockets throughout Turkey. Cultivar Hamzadere and Osmancık 97 are important rice cultivars that are resistant against lodging and are moderately tolerant to blight and  root rot along with high yield potential. To synchronise uniform stand, planting of rice seedlings are preferred over direct seeding. Rice is very sensitive to water shortage. Good stand results in good crop. The study aimed to identify a system that could induce high tillering and acclerated growth of plants during early stages of growth at seedling stage. The seeds of two cultivars were primed on semi solid agar gelled MS medium or MS medium having dissimilar doses of N6-Benzyladenine (BA) and Naphthaleneacetic acid (NAA) used singly or in combination to improve earlier seedling growth and tillering. The results of the study showed variable effects of priming on growth components and parameters depending on concentration of plant growth regulators used. BA+NAA priming was inhibitory to the growth and development of seedlings’ shoots and roots of both cultivars. BA treatments used singly were comparatively better;  however, the treatments that contained NAA used singly in any concentration or MS medium used singly had significant edge over rest of the treatments. A significant and distinct improvement was observed in terms of all growth parmeters including number of tillers per seedling. It is concluded that priming on nutrient rich MS medium  could help in uniformity of growth and seedling development without any bottleneck  and improved yield.
Keywords: agar gelled priming; auxins; cytokinins; multiplication; stress; tillers; fresh weight; dry weight